Systems to Address Burnout and Support Well‐being: Implications for Intensive Care Unit Nurses. (2020) - Rushton, Cynda Hylton; Pappas, Sharon
ABSTRACT : N/A: Burnout, a syndrome resulting from chronic job‐related stress in the workplace, is an extensive problem among clinicians working in health care organizations. The 3 dimensions of burnout include emotional exhaustion, depersonalization, and loss of a sense of professional efficacy. Approximately 35% of all nurses experience symptoms of burnout. Critical care nurses are at risk for chronic job stress because of the complexity and pace of the critical care environment. Addressing the individual and systems‐related factors that stem from the work environment is essential in order to achieve well‐being among all clinicians. Strategies aimed at fostering individual resilience and well‐being must be coupled with systemic solutions that create a work environment that removes impediments to ethically grounded practice, restores fulfillment achieved in clinical practice, and fosters resilience and well‐being.